2008
DOI: 10.1007/s10637-008-9121-8
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the therapeutic efficacy of tripeptide tyroserleutide (YSL) for human hepatocarcinoma by in vivo hollow fiber assay

Abstract: Tyroserleutide (YSL), extracted from spleen of pigs, is a tripeptide that has shown therapeutic efficacy in an experimental BEL-7402 human hepatocarcinoma model. The hollow fiber assay (HFA) is a solid tumor model for large-scale screening of potential anticancer compounds that minimizes expenditures of materials, time, and money. Tumor cells are cultivated within biocompatible, semipermeable hollow fibers, which are implanted in immunosuppressed mice. In this study, the HFA was used to investigate the therape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…Li et al. used HFA to test the therapeutic efficacy of tripeptide tyroserleutide (YSL) in five different human HCC‐cell lines (Li et al. 2008).…”
Section: Xenograft Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al. used HFA to test the therapeutic efficacy of tripeptide tyroserleutide (YSL) in five different human HCC‐cell lines (Li et al. 2008).…”
Section: Xenograft Modelsmentioning
confidence: 99%
“…The ability for multiplexing reduces the number of laboratory animals; this combined with the shorter evaluation time and reduced consumption of test agents makes it an economically interesting method . Li et al used HFA to test the therapeutic efficacy of tripeptide tyroserleutide (YSL) in five different human HCC-cell lines (Li et al 2008). The mice were implanted with three hollow fibres containing BEL-7402, SMMC-7721 and Hep3B or two hollow fibres with HepG2 and SK-HEP-1, and were treated with YSL.…”
Section: Xenograft Modelsmentioning
confidence: 99%
“…Because HFA can provide the real in vivo environment,in accordance with the action characteristics of natural products involving traditional Chinese herbs, HFA has potential broad application prospects in antitumor research field of traditional Chinese herbs and other natural products [3]. Moreover, a large number of research results showed that HFA was also an effective method to quickly research pharmacodynamics (e.g., Pervilleines B and C [4], Paclitaxel and Pacliex [5], C1311 and SJG-13 [6], ASI-145 [7], YSL [8], TAS-102 [9]) and mechanism (e.g., PCNA and Rb [10], p16 [11], NF-kappa B [12]) of antitumor drugs.…”
Section: Introductionmentioning
confidence: 99%
“…The concentration of nanoparticles was selected by referring to previous studies. 36 After 24 h and 48 h, the washed cells were treated with CCK-8 reagent. Cells that were not treated with NPs were used as a negative controls.…”
Section: Methodsmentioning
confidence: 99%